2018
DOI: 10.4103/ijdr.ijdr_195_17
|View full text |Cite
|
Sign up to set email alerts
|

Nature and pattern of primary teeth extractions in a tertiary care hospital setting in South India

Abstract: This study demonstrates a high prevalence of untimely primary teeth extractions in young children and dental caries continues to be the leading cause. It clearly reflects on the lack of infant oral health care, the inadequacy of awareness and underutilization of oral health services among children in India.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
10
1
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 0 publications
6
10
1
2
Order By: Relevance
“…The percentage of extracted teeth in the mandible is about two-folds of those in the mandible, and molar teeth are commonly extracted 1 . A single-center study reported that the most common type of tooth extracted is the primary first molar, followed by the first incisor 2 . Caries is the most common cause of extracted teeth in children aged two to 13 years, which accounted for 57.4% of participants in one study 3 .…”
Section: Discussionmentioning
confidence: 99%
“…The percentage of extracted teeth in the mandible is about two-folds of those in the mandible, and molar teeth are commonly extracted 1 . A single-center study reported that the most common type of tooth extracted is the primary first molar, followed by the first incisor 2 . Caries is the most common cause of extracted teeth in children aged two to 13 years, which accounted for 57.4% of participants in one study 3 .…”
Section: Discussionmentioning
confidence: 99%
“…Many studies reveal that dental diseases such as caries, periodontal diseases, and trauma remain as the primary etiological factors early loss of teeth among all age groups which can lead to space loss 13, [21][22][23] . Evidence suggests that the most frequently extracted tooth in the maxillary arch is the maxillary primary incisor in 2-5 years age group and first primary molar in [6][7][8][9][10][11][12][13][14][15] years age group 24 . Similar findings have been reported in literature suggesting the most frequently extracted tooth to be the first primary molar in the mixed dentition period 25 .…”
Section: Introductionmentioning
confidence: 99%
“…In developing countries such as Mexico, where access to and provision of dental health services is limited because of the lack of supplies, dental extraction is often the treatment of choice for primary teeth. [9] Premature tooth loss has been defined as the loss of a dental organ before the time of natural exfoliation. [10] Studies conducted around the world on premature tooth loss reveal a prevalence ranging from 8.5% to 51.0%.…”
Section: Introductionmentioning
confidence: 99%
“…[6] The most common cause of this event is dental caries, and other factors reported include trauma, ectopic eruption, congenital disorders, and orthodontic considerations. [11–13] Premature loss can cause difficulty with the proper development of mastication, and also disorders in phonation and a decrease in the perimeter of the temporary dental arch, favoring alterations in craniofacial growth. In particular, a reduction in the length of the dental arch can cause crowding and tooth impaction, and increase the need for orthodontic treatment.…”
Section: Introductionmentioning
confidence: 99%